Inhibition of leukotriene B4-induced CD11B/CD18 (Mac-1) expression by BIIL 284, a new long acting LTB4 receptor antagonist, in patients with rheumatoid arthritis. Issue 2 (13th January 2004) - Alten, R; Gromnica-Ihle, E; Pohl, C; Emmerich, J; Steffgen, J; Roscher, R; Sigmund, R; Schmolke, B; Steinmann, G
Abstract : Background: Leukotriene B4 (LTB4 ) has a key role in the pathophysiology of rheumatoid arthritis (RA). Objective: To investigate the inhibition of ex vivo LTB4 -induced Mac-1 (CD11b/CD18) expression in leucocytes of patients with RA by the new oral LTB4 receptor antagonist BIIL 284. Methods: The pharmacokinetics and inhibition of LTB4 -induced Mac-1 expression of BIIL 284 were characterised in 26 adult patients with RA who were treated with BIIL 284 25 mg, 150 mg, or placebo given once a day for 14 days according to a double blind, randomised, parallel group design. Results: Tmax of BIIL 315 in plasma (main metabolite and active principle of BIIL 284 in plasma) was achieved about four hours after drug administration, and Cmax, ss and AUC0–6h, ss increased in proportion to the dosage. 100% inhibition of LTB4 -induced MAC-1 expression was reached after two hours (150 mg) or four hours (25 mg), showing a statistically significant difference in comparison with placebo (p<0.005). A longlasting dynamic effect was seen consistently even when plasma concentrations declined to very low values 24 hours after administration. Secondary clinical efficacy end points remained unchanged probably owing to the short duration of treatment. Adverse events (AEs) were reported in 12 patients during the study. No serious AEs or laboratory AEs were seen. Conclusions: Both the 25 mg and 150 mg doses of BIIL 284 safely and effectively inhibit Mac-1 expression on neutrophils; thus longer treatment with BIIL 284 may result in clinical benefit for patients with RA.